EFFECT OF DIFFERENT CROPPING SYSTEMS ON THE GROWTH AND YIELD OF SWEET CORN AND SWEET POTATO - Evangelio, Luvimin A.; Rosario, Elpidio L. (Annals of Tropical Research, 1981)
Sweet corn and sweet potato were grown under 13 different cropping treatments. Double rows spaced at 0.3 m with interval row spacing of 1.0 m appeared to be the optimum treatment combination with a mean yield of 21.99 t/ha. Under this scheme, yield increases of 75% and 66% were noted in sweet corn and sweet potato, respectively. Land equivalent ratio (LER) was significantly affected by cropping systems. Both alternate cropping scheme and double row arrangement had LER greater than 1. The LER values obtained on yield as fraction of monoculture checks for sweet corn and sweet potato indicated a net positive effect between the two cropping patterns. LER notably decreased as the interval row spacing was increased from 1.0 m to 2.0 m for double rows spaced at 0.3 m and 0.5 m. Growth and yield parameters of sweet potato that were significantly affected by the different cropping treatments were: leaf area per plant, leaf area index (LAI), length of vines at harvest, yield of marketable tubers per hectare, yield of tubers per plant, total dry matter (TDM) per plot, and harvest index (HI). On sweet corn, leaf area per plant, LAI, date to green maturity, weight of ears per plant, TDM per plant and HI were the growth and yield parameters that were significantly affected by the cropping treatments. Parameters that were not significantly affected by the cropping treatments used for sweet potato were: length of vine 30 days after planting, number of marketable and non-marketable tubers per plant, and yield of non-marketable tubers per hectare. Cropping systems did not have a significant effect on plant height of sweet corn 30 and 60 days after planting.